Criteria for the minimum operation length of internal forces as a function of the development of an optimum structure of machinery structural components - Fligiel, Marek; Patyk, Radosław (Zielona Góra: Uniwersytet Zielonogórski)
The present study analyzes the operation length of internal forces (DDSW) understood as the length of the flow of internal forces along the shortest possible internal routes. The operation length of internal forces is determined on the basis of stresses and the given volume in the constructional space. The minimum DDSW of the structure satisfies the criterial conditions of the most rigid structure, where the potential energy of deformation and the deformation energy potential is the same in the whole volume and thus the potential gradient is zero.
Keywords: operation length of internal forces; topological optimization; optimization criteria